Analisis Sensitivitas Respon Mahasiswa Terhadap Perluasan Merek Shampo Lifebuoy - Indri Nuramalia; Z Mawardi Effendi (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the level of sensitivity of students to brand expansion of Lifebuoy shampoo at the State University of Padang and to find out the direction of the response of UNP students to brand expansion of Lifebuoy shampoo. This type of research is a survey with a descriptive approach. The population of this research is the students of Padang State University (UNP). The sample in this study was based on the Chocran formula as many as 100 respondents who were selected using the Non-Probability sampling method and purposive sampling technique. Using primary data obtained through distributing questionnaires to UNP students with certain criteria. The method used is the analysis of the direction of the consumer's response by calculating the strength of the response and stimuli as well as the sensitivity analysis of the response. The results showed that (1) The sensitivity of the response of UNP students from bar soap to lifebuoy shampoo was 2.41. because the size of this sensitivity is greater than 1, the sensitivity is considered a sensitive measure. (2) the response strength of UNP students from Lifebuoy bath soap to Lifebuoy brand shampoo is negative 157. Keywords : brand extension, sensitivity, direction of response